Roots navigate around decay regions by sensing local pH gradients - Zhulatai Bao; Huihui Wang; Ai Zhang; Ruxi Gao; Wen Gu; Ni Fan; Jiří Friml; Yuzhou Zhang (Science, 2026)
Plant tropisms enable roots to navigate complex soils by responding to directional environmental cues. Biological decay, although central to nutrient cycling, also creates microbially active and potentially hostile niches. In this work, we identified “saprotropism,” a previously unrecognized growth response that enables roots to actively bend away from decaying plant-derived matter. Fungal-driven microbial decomposition released organic acids and formed stable pH gradients in surrounding soil, allowing roots to pinpoint decay without direct contact. Root epidermal cells sensed this acidic gradient through the root meristem growth factor peptide-receptor module, converting external pH asymmetry into asymmetric abscisic acid (ABA) distribution. ABA asymmetry drove microtubule reorganization, which was decoded into decay-avoidant root bending. Together, these findings establish microbial decay–derived chemical gradients as an instructive signal for root navigation and expand the framework of microbe-soil-plant communication.